2017
DOI: 10.4314/ahs.v17i2.21
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, severity and factors associated with peripheral neuropathy among newly diagnosed diabetic patients attending Mulago hospital: a cross-sectional study

Abstract: Aims: To determine the prevalence and associated risk factors of diabetic peripheral neuropathy (DPN) among newly diagnosed diabetes mellitus patients in Mulago Hospital. Methods: A cross-sectional study was conducted among 248 newly diagnosed adult diabetic patients. Using the standard Neuropathy Symptom Score (NSS) and Neuropathy Disability Score (NDS) criteria, we screened them for neuropathy. Data on the socio-demographics, age, duration of symptoms and history of diabetic ulcer were analyzed using a multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
4
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 28 publications
(16 reference statements)
4
34
4
2
Order By: Relevance
“…Totally, 1,278 studies were retrieved, of which, 1,261 studies were found from six international databases and the remaining 17 were through manual search. Databases includes; PubMed 161 [44,45], 2 research paper from Egypt [46,47],the remaining was from Ghana [15],Uganda [48],and Tanzania [49]. The highest prevalence of diabetic peripheral neuropathy (83.4%) and the lowest (7.5%) were reported from Nigeria.…”
Section: Search Resultsmentioning
confidence: 99%
“…Totally, 1,278 studies were retrieved, of which, 1,261 studies were found from six international databases and the remaining 17 were through manual search. Databases includes; PubMed 161 [44,45], 2 research paper from Egypt [46,47],the remaining was from Ghana [15],Uganda [48],and Tanzania [49]. The highest prevalence of diabetic peripheral neuropathy (83.4%) and the lowest (7.5%) were reported from Nigeria.…”
Section: Search Resultsmentioning
confidence: 99%
“…A total of 23 studies with 269,691 study participants were included in this meta-analysis. Overall information regarding the prevalence of DPN in DM patients was obtained from various countries across Africa including 10 studies from Nigeria [14, 18-20, 22, 37-41], four from Ethiopia [16,24,42,43], two from Cameroon [23,44], two from Sudan [45,46], two from Egypt [47,48], and one each from Ghana [15], Uganda [49], and Tanzania [50]. The highest and lowest prevalence of DPN was 83.4% [22] and 7.5% [41] respectively, which were reported from Nigeria.…”
Section: Baseline Characteristics Of the Included Studiesmentioning
confidence: 99%
“…19 Mientras que otros estudios realizados en países de bajos a medianos ingresos como India y Pakistán encontraron prevalencia de 10,5 % a 29 %. 20,21 En nuestro país, no hay ningún estudio que haya evaluado la prevalencia de NDP en pacientes con reciente diagnóstico de DM; y en América Latina, solo se ha realizado un estudio similar en la población argentina. Sereday y col. 22 encontraron una prevalencia de NDP de 27,5 % en pacientes con DM de diagnóstico reciente.…”
Section: Discussionunclassified